A high-efficient and stable artificial superoxide dismutase based on functionalized melanin nanoparticles from cuttlefish ink for food preservation. (January 2023) - Liang, Yanmin; Han, Yaru; Dan, Jie; Li, Runli; Sun, Hao; Wang, Jianlong; Zhang, Wentao
Graphical abstract: Highlights: Cu-NMPs (Cu-Melanin Nanoparticles) were prepared by combining NMPs with Cu 2+ . Cu-NMPs mimics the structure of natural Superoxide dismutase. Cu-NMPs as Superoxide dismutase mimic enzyme with significant activity. Incorporated Cu-NMPs improves the physicochemical properties of carrageenan film. The shelf life of cherry tomatoes is significantly extended by Carr/Cu-NMPs films. Abstract: Natural superoxide dismutase (SOD), consisting of proteins and metal cofactors, is widely used in food preservation because of its good antioxidant activity. However, due to the poor stability of SOD enzyme, its activity was reduced in the process of moving into the film, resulting in limited application. Based on the structure of the active site of the natural enzyme, Cu 2+ was used to functionalize the melanin nanoparticles (NMPs) in ink of cuttlefish, and an SOD-like nanozyme (Cu-NMPs) with high stability, high activity and strong free radical scavenging capacity was constructed. In order to apply the constructed simulated enzyme to food preservation, the simulated enzyme was embedded into carrageenan (Carr) films to prepare the composite film for food packaging. The results showed that when the concentration of Cu-NMPs was 10 μg/mL, the ·O2 – rate could reach more than 80 %, the activity exceeded that of 60 U/mL natural SOD. In addition, the fresh-keeping test of cherry tomatoes showed that Carr/Cu-NMPs composite film extended the storage time of cherry tomatoes by more 3 days. Therefore, the present work showed that nanozymes with advanced catalytic capabilities can be constructed by metal ions and NMPs, thus successfully combined with food packaging for food preservation.